Cytotoxic acylphloroglucinols from the aerial parts of Hypericum hirsutum L. (Hypericaceae) - Zlatina Kokanova-Nedialkova; Georgi Momekov; Paraskev T. Nedialkov (Pharmacia)
A phytochemical investigation of the dichloromethane extract of the aerial parts of Hypericum hirsutum L. led to isolating the main polyprenylated acylphloroglucinols (1 and 2). The compounds were identified employing spectral methods (HRMS, 1D, and 2D NMR, IR, UV) as adsecohyperforin (1) and secohyperforin (2), respectively. The MS/MS fragmentation of both compounds and NMR spectral data of 1 are described here for the first time. These natural products were found for the second time in a plant source. The cytotoxicity of isolated compounds was established on a panel of tumor cell lines (MDA-MB, EJ, and HL-60) and was determined using MTT-based assays. Both components showed higher cytotoxicity (IC50 = 0.27–4.85 µM) than the positive control etoposide (IC50 = 1.27–8.42 µM), making them promising candidates for new chemotherapeutic drugs.